2018
DOI: 10.33369/dr.v14i1.4282
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Limbah Pelepah Sawit Sebagai Pakan Ternak Sapi Pada Kelompok Pemuda Tani Tunas Muda

Abstract: The prevalent problem of partnership is the difficulty of supplying green feed. Palm oil frond was the most available palm oil waste for feed utilization by partnership because both partners were located in palm oil plantation area. For optimum feed utilization, palm oil frond was to undergo particular process through ammoniation with urea and fermentation with MOL (local microorganism) from cow manure. The objective of this activity was to introduce the processing technology of palm oil frond by ammoniation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
1
1
1
6
Order By: Relevance
“…These results are in accordance with research conducted by Jarmuji et al (2017) who obtained DM consumption of 3.12% body weight in kaur cattle fed palm frond rations and Sakura Block. The same result was obtained by Batubara (2003) that the consumption of DM in cattle fed palm fronds ration was 3.02% of body weight, but this value was higher than that obtained by Nurhaita et al (2014) who obtained a DM consumption of 2.51% -2.76% of body weight in cattle fed ammoniated palm fronds ration. Orskov and Ibrahim (1991) argued that the consumption of DM for beef cattle ranged from 2.0-3.0% of body weight.…”
Section: The Effect Of Sakura Block Plus On On Ration Consumptionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in accordance with research conducted by Jarmuji et al (2017) who obtained DM consumption of 3.12% body weight in kaur cattle fed palm frond rations and Sakura Block. The same result was obtained by Batubara (2003) that the consumption of DM in cattle fed palm fronds ration was 3.02% of body weight, but this value was higher than that obtained by Nurhaita et al (2014) who obtained a DM consumption of 2.51% -2.76% of body weight in cattle fed ammoniated palm fronds ration. Orskov and Ibrahim (1991) argued that the consumption of DM for beef cattle ranged from 2.0-3.0% of body weight.…”
Section: The Effect Of Sakura Block Plus On On Ration Consumptionsupporting
confidence: 82%
“…Consumption of DM based on the metabolic weight of Kaur cattle fed with palm fronds supplemented with Sakura Block Plus ranged from 101.34 to 103.13 g/head/day. This consumption value is higher compared to the findings of Nurhaita et al (2014), who reported a consumption of 93.13 g/head/day based on the metabolic weight of cattle fed with 50% palm fronds and 50% concentrate.…”
Section: The Effect Of Sakura Block Plus On On Ration Consumptioncontrasting
confidence: 69%
“…Supaya dapat dimanfaatkan secara optimal sebagai pakan ternak pelepah sawit harus diolah terlebih dahulu. Pengolahan secara fisik, kimia dan biologi mampu meningkatkan nilai nutrisi dan kecernaan pelepah sawit, (Nurhaita, Definiati, & Suliasih, 2016). Bahan baku pakan kian dirasakan penting, apalagi kalau melihat struktur biaya produksi peternakan.…”
Section: Pendahuluanunclassified
“…Pada skala komersial, pelepah kelapa sawit diambil lidinya untuk berbagai material, ada juga di beberapa penelitian skala cukup besar yang menggunakan pelepah ini sebagai bahan pakan ternak. Menurut Nurhaita et al (2016), pakan dari pelepah sawit olahan cukup disukai ternak sehingga menjadi solusi dalam masalah kesulitan pakan hijauan. Meskipun demikian, pelepah biasanya hanya diletakkan di antara barisan tanaman kelapa sawit (gawangan mati) dan dibiarkan melapuk dengan sendirinya.…”
Section: Pendahuluanunclassified